Structural investigations of the p53/p73 homologs from the tunicate species Ciona intestinalis reveal the sequence requirements for the formation of a tetramerization domain. (25th November 2015) - Heering, Jan; Jonker, Hendrik R. A.; Löhr, Frank; Schwalbe, Harald; Dötsch, Volker
Abstract: Most members of the p53 family of transcription factors form tetramers. Responsible for determining the oligomeric state is a short oligomerization domain consisting of one β‐strand and one α‐helix. With the exception of human p53 all other family members investigated so far contain a second α‐helix as part of their tetramerization domain. Here we have used nuclear magnetic resonance spectroscopy to characterize the oligomerization domains of the two p53‐like proteins from the tunicate Ciona intestinalis, representing the closest living relative of vertebrates. Structure determination reveals for one of the two proteins a new type of packing of this second α‐helix on the core domain that was not predicted based on the sequence, while the other protein does not form a second helix despite the presence of crucial residues that are conserved in all other family members that form a second helix. By mutational analysis, we identify a proline as well as large hydrophobic residues in the hinge region between both helices as the crucial determinant for the formation of a second helix. Abstract : PDB Code(s):2MW4